Barley Stem Rust Resistance Genes: Structure and Function - Andris Kleinhofs; Robert Brueggeman; Jayaveeramuthu Nirmala; Ling Zhang; Aghafakhr Mirlohi; Arnis Druka; Nils Rostoks; Brian J. Steffenson (The Plant Genome, 2009)
Rusts are biotrophic pathogens that attack many plant species but are particularly destructive on cereal crops. The stem rusts (caused by ) have historically caused severe crop losses and continue to threaten production today. Barley ( L.) breeders have controlled major stem rust epidemics since the 1940s with a single durable resistance gene . As new epidemics have threatened, additional resistance genes were identified to counter new rust races, such as the complex locus against races QCCJ and TTKSK. To understand how these genes work, we initiated research to clone and characterize them. The gene encodes a unique protein kinase with dual kinase domains, an active kinase, and a pseudokinase. Function of both domains is essential to confer resistance. The and genes are closely linked and function coordinately to confer resistance to several wheat ( L.) stem rust races, including the race TTKSK (also called Ug99) that threatens the world's barley and wheat crops. The gene encodes typical resistance gene domains NBS, LRR, and protein kinase but is unique in that all three domains reside in a single gene, a previously unknown structure among plant disease resistance genes. The gene encodes an actin depolymerizing factor that functions in cytoskeleton rearrangement.